KOMITMEN ORGANISASI SEBAGAI PEMODERASI PENGARUH MOTIVASI, KEPUASAN KERJA, DAN KOMPETENSI PADA KINERJA AUDITOR (Studi Empiris Pada Kantor Akuntan Publik Di Bali) - Lestari, Ni Luh Putu Ratna Wahyu; Yadnyana, I Ketut; Astika, Ida Bagus Putra (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.01.TAHUN 2017, 2016)
This study aims to obtain empirical evidence moderation organization's commitment to the influence of motivation, job satisfaction, and competence of auditors in the performance of auditors. Research on the relationship between the auditor motivation, job satisfaction, and competence in the performance of auditors has been done before which shows the results of different. The difference results of these studies completed through a contingency approach (contingency approach) and organizational commitment variable. This study uses primary data were collected by using a questionnaire. The number of samples in the study were as many as 62, were selected based method nonprobability sampling with purposive sampling technique. Data analysis technique used is moderation regression analysis (MRA). The result is there is no moderation of organizational commitment on motivational influence on the performance of auditors and job satisfaction in the performance of auditors. There moderation organizational commitment that strengthens the influence of the competence of auditors in the performance of auditors.
Keywords: auditor performance, motivation, job satisfaction, auditor competence, commitment to the organization